Eligibility for low-dose computerized tomography screening among asbestos-exposed individuals - Fitzgerald, Natalie R.; Flanagan, William M.; Evans, William K.; Miller, Anthony B. (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVES ': 'The study aimed to incorporate an estimate of risk for asbestos exposure in the Canadian Cancer Risk Management Lung Cancer (CRMM-LC) microsimulation model. ' ' METHODS ': 'In CRMM-LC, a 3-year probability of developing lung cancer can be derived from different risk profiles. An asbestos-exposed cohort was simulated and different scenarios of low-dose computerized tomography (LDCT) screening were simulated. ' ' RESULTS ': 'As annual LDCT screening among non-asbestos-exposed individuals is less cost-effective than biennial screening, all the scenarios modeled for an asbestos-exposed cohort were biennial. For individuals with a two-fold risk of asbestos-induced lung cancer to be eligible for biennial LDCT screening, a smoking history of ≥15 pack-years would be necessary. For non-smokers with asbestos exposure resulting in a relative risk (RR) for lung cancer, it is not cost-effective to screen those with a RR of 5, but it is cost-effective to screen those with a RR of 10 (the heavily exposed). ' ' CONCLUSION ': 'Asbestos-exposed individuals with an estimated two-fold or more risk of lung cancer from asbestos-exposure are eligible for LDCT screening at all ages from 55–74 years if they have a cigarette smoking history of ≥15 pack-years. Asbestos-exposed individuals who are lifelong non-smokers are eligible for LDCT screening at all ages from 55–74 years if they have accumulated a degree of asbestos exposure resulting in an estimated risk of lung cancer of ≥10.
Keywords: asbestos; asbestos exposure; cancer; cost-effectiveness; CT; exposure; low-dose computerized tomography; lung cancer; mathematical modeling; microsimulation; risk factor; smoking